Delayed Onset of Pseudoaneurysm in Brachial Stab Wound Trauma: A Case Report - Tangkilisan, Adrian; Sukanto, Wega; Tamburian, Christha Z.; Paat, Rigel K.; Pontoh, Pramijaya R. (Medical Scope Journal, 2026)
Abstract: Pseudoaneurysms of the extremity are rare and may present acutely or subacutely. Very rarely, the presence of thromboembolism in the aneurysm can result in terminal ischemia, gangrene, and amputation. Only early diagnosis and treatment can prevent progression to significant disability. This case report described a 36-year-old male referred to the hospital with a complaint of a lump in the upper left arm for two months before admission. The patient reported a history of being punctured by a nail, and one week later, an enlarging lump appeared. The patient also complained of a lump on the right chin for one month before hospital admission. The patient was then diagnosed with an impending rupture of the left brachial pseudoaneurysm due to a puncture wound in the left brachial and was scheduled for arterial repair. Although the diagnosis and treatment of the patient were delayed for two months and treated surgically, no immediate or late complications were seen. This case underscores the crucial role of timely diagnosis and surgical treatment, as upper extremity aneurysms can cause severe decreases in function and lead to the loss of an arm or fingers. The successful surgical reconstruction in this case is a motivating example of the preferred treatment for such patients. Keywords:  pseudoaneurysm; brachial artery; repair artery; delayed onset